Macroporous foam of reduced graphene oxides prepared by lyophilization - Lu, Xiaomei (2013)
In this study, we demonstrate that water-soluble grafted polymer polyfluorene-grafted-poly(sulfobetainemetahcrylate) (PF-g-PSBMA) allows chemically reduced GO sheets dispersed in aqueous solution due to its ability to stably disperse hydrophobic rGO sheets. Based on the stable rGO/PF-g-PSBMA dispersion, macroporous graphene foam can be simply obtained by lyophilization process (freeze-drying). The resulting composite foam exhibits three-dimensional macroporous structure with high specific surface area and can easily re-dissolve into water. Also, the stable rGO/PF-g-PSBMA dispersion allows solution-based fabrication of thin-film graphene devices. Moreover, PF-g-PSBMA can be removed from rGO foam or film by thermal annealing, and the conductivity of rGO film can be greatly enhanced likely due to its annealing ability.